2012
DOI: 10.3762/bjnano.3.51
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Fe/Fe3O4-nanoparticle-bound SN38 as carboxylesterase-cleavable prodrug for the delivery to tumors within monocytes/macrophages

Abstract: SummaryThe targeted delivery of therapeutics to the tumor site is highly desirable in cancer treatment, because it is capable of minimizing collateral damage. Herein, we report the synthesis of a nanoplatform, which is composed of a 15 ± 1 nm diameter core/shell Fe/Fe3O4 magnetic nanoparticles (MNPs) and the topoisomerase I blocker SN38 bound to the surface of the MNPs via a carboxylesterase cleavable linker. This nanoplatform demonstrated high heating ability (SAR = 522 ± 40 W/g) in an AC-magnetic field. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…The challenging task of loading hydrophobic chemotherapy drugs onto the antibody-labelled biosilica was solved by electrostatic adsorption of drug-loaded, positively charged liposomes and micelles for later deployment. Up to 85.8% DL% was achieved, which is higher than has been reported for other nanoparticle systems 36 . For both liposomal and micellar nanocarriers adsorbed to diatom biosilica, release studies showed that more than the required effective drug dose was released into the culture medium, indicating the potential to kill targeted cells.…”
Section: Discussionmentioning
confidence: 49%
“…The challenging task of loading hydrophobic chemotherapy drugs onto the antibody-labelled biosilica was solved by electrostatic adsorption of drug-loaded, positively charged liposomes and micelles for later deployment. Up to 85.8% DL% was achieved, which is higher than has been reported for other nanoparticle systems 36 . For both liposomal and micellar nanocarriers adsorbed to diatom biosilica, release studies showed that more than the required effective drug dose was released into the culture medium, indicating the potential to kill targeted cells.…”
Section: Discussionmentioning
confidence: 49%
“…Treatment using the SN38-dextran loaded Mo/Ma cells in conjunction with doxycycline showed 10% longer survival time in a murine disseminated pancreatic cancer model, in comparison to the SN38 control group. To further optimize Mo/Ma based targeted delivery, a nanoplatform composed of Fe/Fe 3 SO 4 magnetic nanoparticles (MNPs) and SN38 bound to the outer layer of MNPs via a carboxylesterase cleavable linker was synthesised and was loaded into the Mo/Ma cells [109]. The MNPs showed low toxicity to the Mo/Ma cells even at high concentrations (up to 320 μg/ml), thus allowing high drug loading efficiency in the Mo/Ma cells.…”
Section: Bioengineered Cells As Drug Carriersmentioning
confidence: 99%
“…Bioengineered and tumour-homing cells have been utilised as targeted delivery carriers of both SN38 prodrugs and the prodrugactivating enzyme [107][108][109]. For example, RAW 264.7 cells (mouse monocytes/macrophage-like cells, Mo/Ma) for inducible expression of carboxylesterase have been engineered.…”
Section: Bioengineered Cells As Drug Carriersmentioning
confidence: 99%
“…[9][10][11] In addition, magnetic hyperthermia treatments last for several minutes and hours. A more effective way to destroy cancer cells is to utilize the nanoparticles as little magnetically driven drill bits.…”
Section: Introductionmentioning
confidence: 99%